A Systematic Review: The Effectiveness of Vitamin D Supplementation on Tuberculosis Spondylitis - Aila Mustofa; Hamid Faqih Umam; David Noor Umam (Future Science, 2024)
Introduction: Tuberculosis remains a major global health problem. About 50% of musculoskeletal tuberculosis involves the spine. Vitamin D deficiency is related to a higher risk of tuberculosis infection. Vitamin D has a potential benefit on the immune system during tuberculosis spondylitis. Methods: A systematic review was performed using PRISMA flowchart in five databases to identify articles until July 24th 2024. The risk of bias was evaluated by modified Jadad Scale. Results: Three articles using randomized controlled trials, with a total 162 patients. High-dose vitamin D supplementation (5.000IU and 10.000IU) showed significant efficacy in several indicators. Serum vitamin D levels increased to 38.49 ng/mL. There was an improvement in immune response (TLR2, TLR4) and a decrease in inflammatory markers (TGF-?1, IL-10, IL-17, IL-23, CRP, and ESR). High-dose vitamin D administration was shown to increase overall efficacy (95.65% vs. 80.43%, p<0.05), reduce pain, and improve spinal cord injury grade and activities of daily living. No difference in adverse events was observed in the intervention group. Conclusion: Vitamin D supplementation may improve the efficacy of tuberculosis spondylitis treatment. Further research is needed to determine the recommended dose and duration of supplementation in clinical practice.